Pengaruh Pemberian Agens Hayati Terhadap Intensitas Penyakit Karat Beberapa Varietas Kedelai Hitam - Gayuh Prasetyo Budi; Teguh Pribadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Black soybean (G. max (L.) Merr.) is an important food crop and has a high nutritional content. Demand for this commodity is increasing. National soybean demand in 2015 about 2.6 million tons but domestic production only 982,967 tons. One of the obstacles to increasing black soybean production is Asian soybean rust disease caused by P. pachyrhizi. The susceptibility of black soybean to rust makes the farmers often use chemical fungicides to control it. Alternative control of rust leaves that suitable for the environment is through the selection of more resistant varieties of rust and the application of biological agents of Corynebacterium sp. and Plant Growth Promoting Rhizobacteria (PGPR). The research was conducted in endemic area of ​​ Asian soybean rust disease, using Complete Randomized Design 2 factors. Factor 1 varieties of black soybeans consists of V1: Detam 1, V2: Detam 3, V3: Detam 4 and Factor 2 biological agents consist of: control, Corynebacterium sp. and PGPR with 3 replications. The results showed that Detam 1 varieties produced the most massive seeds: 6.86 g plant-1. Corynebacterium sp. and PGPR treatment can significantly reduce the intensity of Asian soybean rust disease compared to controls. The intensity of rust disease in Corynebacterium sp. (11.7%), PGPR (8.9%), control (33.9%). Both soybean varieties and biological agents showed no interaction in all observed variables.